Effects of Calcium Chloride Crosslinking Solution Concentration on the Long-Term Cell Viability of 16HBE14o- Human Bronchial Cells Embedded in Alginate-Based Hydrogels - Nathan Wood; Esther I. Doria; Taieba Tuba Rahman; Wanhe Li; Zhijian Pei; Hongmin Qin (Biomimetics)
In this preliminary study, the long-term effects of calcium chloride crosslinking concentration on viability of 16HBE14o- human bronchial epithelial cells embedded in alginate-extracellular matrix (ECM) or alginate–methylcellulose–ECM hydrogels have been investigated. There is currently a limited understanding regarding the effects of crosslinking solution concentration on lung epithelial cells embedded in hydrogel. Furthermore, the effects of calcium chloride concentration in crosslinking solutions on other cell types have not been reported regarding whether the addition of viscosity and stiffness tuning agents such as methylcellulose will alter the responses of cells to changes in calcium chloride concentration in crosslinking solutions. While there were no significant effects of calcium chloride concentration on cell viability in alginate–ECM hydrogels, there is a decrease in cell viability in alginate–methylcellulose–ECM hydrogels crosslinked with 300 mM calcium chloride crosslinking solution. These findings have implications in the maintenance of 16HBE14o- 3D cultures with respect to the gelation of alginate with high concentrations of ionic crosslinking solution.